KARAKTERISTIK KEKUATAN FATIGUE SAMBUNGAN FRICTION STIR WELDING PADA PADUAN ALUMINIUM 5052 - Adli Dzil Ikram Caecar (2023)
Friction stir welding (FSW) is a method of joining two metals using a rotating pin that produces friction and heat, thus the metal becomes plastic but does not melt entirely and a connection occurs between the two. The advantage of FSW is that it can connect several different types of metals (dissimilar joints) such as aluminum with copper, aluminum with steel, even aluminum with different types of aluminum. This research is a study to determine the strength of friction stir welding joints on Aluminum alloy 5052 based on welded joints fatigue strength. Material of 5 mm thickness is being tested with specified parameters including feed rate of 13 mm/min, shoulder diameter and pin length of 12 mm and 4 mm respectively, spindle speed is 990 rpm, and load variations of 60%, 70%, and 80% from the maximum load. The experimental results indicate that the greater the fatigue load, the lower the cycle obtained. At 80% maximum load, the cycles obtained are 23099, 23214, and 22871. Followed by a 70% maximum load, the cycles obtained are 56251, 49895, and 56377 and with 60% maximum load the obtained. Cycles are 97136, 100579, and 92366 all with a frequency of 10 Hz. The FSW parameters on this research are still less reliable in the field of engineering.